Step
*
1
1
1
2
of Lemma
cos-sin-equation-non-constant2
1. f : ℝ ⟶ ℝ
2. g : ℝ ⟶ ℝ
3. ∀x,y:ℝ. ((x = y)
⇒ (f(x) = f(y)))
4. ∀x,y:ℝ. ((x = y)
⇒ (g(x) = g(y)))
5. u : ℝ
6. v : ℝ
7. f(u) ≠ f(v)
8. ∀x,y:ℝ. (f(x - y) = ((f(x) * f(y)) + (g(x) * g(y))))
9. ¬¬(∃a:ℝ. (a ≠ r0 ∧ (∀x:ℝ. (f(x) = rcos(a * x))) ∧ (∀x:ℝ. (g(x) = rsin(a * x)))))
10. I : Interval
11. iproper(I)
12. r0 ∈ I
13. g' : I ⟶ℝ
14. d(g(x))/dx = λx.g' x on I
15. a : ℝ
16. a ≠ r0
17. ∀x:ℝ. (f(x) = rcos(a * x))
18. ∀x:ℝ. (g(x) = rsin(a * x))
19. d(rsin(a * x))/dx = λx.g' x on I
20. d(rsin(a * x))/dx = λx.rcos(a * x) * a on (-∞, ∞)
⊢ d(rsin(a * x))/dx = λx.a * rcos(a * x) on (-∞, ∞)
BY
{ (DerivativeFunctionality (-1)⋅ THEN Auto) }
Latex:
Latex:
1. f : \mBbbR{} {}\mrightarrow{} \mBbbR{}
2. g : \mBbbR{} {}\mrightarrow{} \mBbbR{}
3. \mforall{}x,y:\mBbbR{}. ((x = y) {}\mRightarrow{} (f(x) = f(y)))
4. \mforall{}x,y:\mBbbR{}. ((x = y) {}\mRightarrow{} (g(x) = g(y)))
5. u : \mBbbR{}
6. v : \mBbbR{}
7. f(u) \mneq{} f(v)
8. \mforall{}x,y:\mBbbR{}. (f(x - y) = ((f(x) * f(y)) + (g(x) * g(y))))
9. \mneg{}\mneg{}(\mexists{}a:\mBbbR{}. (a \mneq{} r0 \mwedge{} (\mforall{}x:\mBbbR{}. (f(x) = rcos(a * x))) \mwedge{} (\mforall{}x:\mBbbR{}. (g(x) = rsin(a * x)))))
10. I : Interval
11. iproper(I)
12. r0 \mmember{} I
13. g' : I {}\mrightarrow{}\mBbbR{}
14. d(g(x))/dx = \mlambda{}x.g' x on I
15. a : \mBbbR{}
16. a \mneq{} r0
17. \mforall{}x:\mBbbR{}. (f(x) = rcos(a * x))
18. \mforall{}x:\mBbbR{}. (g(x) = rsin(a * x))
19. d(rsin(a * x))/dx = \mlambda{}x.g' x on I
20. d(rsin(a * x))/dx = \mlambda{}x.rcos(a * x) * a on (-\minfty{}, \minfty{})
\mvdash{} d(rsin(a * x))/dx = \mlambda{}x.a * rcos(a * x) on (-\minfty{}, \minfty{})
By
Latex:
(DerivativeFunctionality (-1)\mcdot{} THEN Auto)
Home
Index